PREECLAMPSIA AND PRETERM BIRTH AS PREDOMINANT FACTORS OF LOW BIRTH WEIGHT: INSIGHTS FROM A RURAL HOSPITAL IN INDONESIA - Dzakiyyah, Sitisalma Amirah; Rahma, Alissa; Salsabila, Aziza; Agustina, Devi Silvia; Qamariah, Syarifah; Duarsa, Adhi Mahabudi; Cininta, Nareswari Imanadha (Folia Medica Indonesiana, 2025)
Low birth weight (LBW) remains a major public health concern in low-resource and rural settings due to its strong association with neonatal morbidity and mortality. This study aimed to identify maternal determinants associated with LBW in a rural hospital in Indonesia. A retrospective cross-sectional review was conducted on 179 singleton deliveries between January 1st and December 31st, 2024, at Alimuddin Umar General Hospital. Maternal age, parity, anemia, preeclampsia, and gestational age at delivery were obtained from medical records and analyzed using bivariate and multivariate methods. Bivariate analysis showed that preterm birth (p < 0.001) and preeclampsia (p < 0.05) were significantly associated with LBW, whereas maternal age, parity, and anemia showed no significant associations. When adjusted for potential confounders in the multivariate analyses, both preeclampsia (p = 0.019; OR = 4.61; 95% CI: 1.29–16.55) and preterm birth (p < 0.001; OR = 14.60; 95% CI: 5.52–38.57) remained independent predictors of LBW. These findings suggest that preeclampsia and preterm birth are the main contributors to LBW in this setting. Strengthening antenatal care, particularly early detection and management of preeclampsia and prevention of preterm birth, may reduce the burden of LBW. Further studies including nutritional, socioeconomic, and antenatal care variables are recommended to identify independent risk factors more comprehensively.